Mental Health Audit Snapshot 2022 (2022)
The AIS partnered with Orygen to assess the mental health and wellbeing of Australian high performance athletes, coaches and support staff. This is the third audit to be conducted with previous ones undertaken in 2018 and 2020. The information provided from these audits help inform and improve support services and programs such as the AIS Mental Health Referral Network (MHRN).